Species diversity, abundance, and movement of small mammals in the dry evergreen forest at Khao Yai National Park, Thailand - Yuwaluk Chanachai; Anuttara Nathalang; Prateep Duengkae; Ronglarp Sukmasuang (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Chanachai Y, Nathalang A, Duengkae P, Sukmasuang R. 2022. Species diversity, abundance, and movement of small mammals in the dry evergreen forest at Khao Yai National Park, Thailand. Biodiversitas 23: 5892-5901. Small mammals play an integral role in the forest ecosystem. This research was conducted on The Mo Singto Forest Dynamics Plot, Khao Yai National Park. Trapping of small mammals was carried out in June-September 2019 and from January-April 2020 based on a total of 64 Tomahawk for small mammal live traps were systematically placed in an 8×8 grid of 20 m intervals, ripe bananas and palm oil as bait was used. Trap cages were opened for 3 consecutive months per season in each study period covering a total study period of 1 year. The result showed that a total of 4015 individuals from 9 species, 9 genera, 4 families and 3 orders were captured with a sampling effort of 32,555 trap nights. The most common species were Red Spiny Rat (Maxomys surifer), followed by Northern Tree Shrew (Tupaia belangeri), Long-tailed Giant Rat (Leopoldamys sabanus), Indochinese Ground Squirrel (Menetes berdmorei), Asian House Rat (Rattus tanezumi), Indomalayan Niviventer (Niviventer fulvescens), Savile's Bandicoot Rat (Bandicota savilei), (Tamiops mcclellandii), and Short-tailed Gymnure (Hylomys suillus) respectively. Considering the number of small mammals caught, Maxomys surifer was the most abundant, accounting for 61.69% of all mammals caught. The sex ratio was found to somewhat favor females in both seasons. This study indicated that the small mammal diversity was high in the primary dry evergreen forest. These results have important implications not only for conservation but are also useful for further investigation if there is any disturbance or change in the area or any potential disasters that may occur in the future.